Multi-aspect analysis and multi-objective optimization of a solar/geothermal-assisted power and freshwater cogeneration plant. (20th December 2021) - Fan, Guangli; Nedaei, Navid; Farkoush, Saeid Gholami; Guo, Peixi; Lin, Shuchao; Xu, Jin
Abstract: Despite the fact that research on multigeneration and polygeneration systems are available, more efficient and effective systems that fulfill several energy demands at the same time are still needed. Furthermore, efficient use and harvesting of renewable energy sources are critical for global emission reductions. Accordingly, this paper proposes a novel geothermal-solar-based hybrid system for simultaneous power and freshwater production. The overall objective of the study is to model the proposed cogeneration system with energy and exergy exergoeconomic, and economic viewpoints, and obtain the optimum performances of the system using non-dominated sorting genetic algorithm II (NSGA-II) method and LINMAP decision-making approach. According to the obtained results, at the base operating conditions, the exergy destruction rate for the CPVT is the highest with 311.3 k W amongst other components, followed by the RO unit with a value of 159 k W . Also, the net output electricity of the total system and freshwater generation rate are computed to be 775.3 k W and 10.14 k g . s − 1 . Also, for the first optimization scenario ( S U C P − η e x ), the exergy efficiency and sum unit cost of the products are obtained by 42.31 % and 16.32 . G J − 1, respectively. And, the produced electricity and freshwater are computed to be 755.3 k W and. 16.44 k g . s − 1 Highlights: Proposal and study of a newly designed electricity/freshwater co-production system. Smart use of solar and geothermal energies for the performance enhancement. Energy, exergy, exergy costing, and NPV methods together with NSGA-II optimization. The optimum exergy efficiency and unit cost are separately 42.31% and 16.32 /GJ. The optimum payback period of the system is estimated to be 1.07 years.